PEMIDANAAN ANGGOTA MILITER PELAKU PERSETUBUHAN SESAMA JENIS (STUDI PUTUSAN NOMOR 231-K/PM.II-8/AU/XII/2020) - Muhammad Ramadhion Prastopo (Fakultas Hukum Universitas Trisakti, 2022)
These actions are punishable by both disciplinary action and criminal action. For instance, a military member who engages in same-sex sexual activity (gay) may face punishment as a Military Criminal, which includes the following: